Impact of a reduced nicotine standard on young adult appeal for menthol and non-menthol cigarettes. Issue 11 (21st November 2022) - Cohn, Amy M; Cassidy, Rachel; Denlinger-Apte, Rachel; Donny, Eric; Villanti, Andrea C; Hatsukami, Dorothy; Dunn, Delaney; Wyatt, Riley; Niznik, Taylor; Cohen-Davidyan, Tamar; Smith, Michael; Ehlke, Sarah J
Abstract : Introduction: The Food and Drug Administration (FDA) announced its intention to reduce the nicotine content in cigarettes as a strategy to promote cessation and reduce smoking-related harm. A low nicotine product standard will apply to all cigarettes on the market, including menthol cigarettes. In December 2021, the FDA approved a modified risk tobacco product application for menthol and non-menthol flavoured very low nicotine cigarettes (VLNC) from the 22nd Century Group. Notably, experimentation with menthol cigarettes is linked to smoking progression, as well as greater nicotine dependence relative to non-menthol cigarette use. If menthol VLNCs are perceived as more appealing than non-menthol VLNCs, this would indicate that some aspect of menthol may maintain smoking even in the absence of nicotine and FDA's regulatory authority to ban or restrict the sale of menthol cigarettes should apply to reduced nicotine content of cigarettes. In April 2022, the FDA announced proposed rulemaking to prohibit menthol cigarettes, however it is unclear if a menthol prohibition would apply to VLNCs. Methods and analysis: This study will recruit 172 young adult menthol smokers (with a specific subsample of n=40 sexual and gender minority young adults) and measure appeal for smoking experimental menthol and non-menthol VLNCs, and the impact of proposed product standards on tobacco product purchasing behaviour using an Experimental Tobacco Marketplace. Appeal across product standards will be assessed in a controlled laboratory and using ecological momentary assessment. Ethics and dissemination: The protocol was approved by the University of Oklahoma Health Sciences Center Institutional Review Board (#11865). Findings will examine the effects of a reduced nicotine standard and a menthol ban on young adult smoking and will be disseminated through peer-reviewed journal articles and presentations at scientific conferences. Trial registration number: NCT04340947 .